The usability and effect of an mHealth disease management platform on the quality of life of patients with paroxysmal atrial fibrillation – The emPOWERD-AF study. (9th November 2022) - Lazaridis, Charalampos; Bakogiannis, Constantinos; Mouselimis, Dimitrios; Tsarouchas, Anastasios; Antoniadis, Antonios P; Triantafyllou, Konstantinos; Fragakis, Nikolaos; Vassilikos, Vassilios P
Atrial fibrillation (AF) is the most common arrhythmia. myAlgos is an mHealth disease management system consisting of physician-oriented platform and patient-oriented smartphone app. Our purpose was to assess the usability of myAlgos by physicians and patients and the effect of myAlgos on the quality of life (QoL) in patients with paroxysmal AF (PAF). Physicians rated the platform with the Post-Study System Usability Questionnaire (PSSUQ). Patients rated the app with the mHealth App Usability Questionnaire (MAUQ). The e-medicine Platform for Optimizing the Workflow in hEaRt Diseases (emPOWERD-AF) study investigated the effect of myAlgos in PAF patients randomized to full/control version. QoL was measured by the Atrial Fibrillation Effect on QualiTy-of-life (AFEQT) and 5-level EQ-5D (EQ-5D-5L) questionnaires. myAlgos got a PSSUQ score of 2.52 ± 0.36 by five physicians and a MAUQ score of 79.9% by 33 patients. In emPOWERD-AF, 80 patients were randomized 1:1 (58.1 ± 8.7 years, 66% male). The median AFEQT change at 6 months was +2.63% in full version users and −1.63% in controls ( p < .001). The myAlgos platform and app were easy-to-use and improved QoL in patients.